Cellular immune profiling after sequential clofarabine and lenalidomide for high risk myelodysplastic syndromes and acute myeloid leukemia. (2017) - Jain, Prachi; Klotz, Jeffrey; Dunavin, Neil; Lu, Kit; Koklanaris, Eleftheria; Draper, Debbie; Superata, Jeanine; Chinian, Fariba; Yu, Quan; Keyvanfar, Keyvan; Wong, Susan; Muranski, Pawel; et al.
Abstract: Patients with high risk myelodysplastic syndromes (MDS) and acute myelogenous leukemia (AML) are commonly older with multiple co-morbidities, rendering them unsuitable for intensive induction chemotherapy or transplantation. We report preliminary cellular immune profiling of four cases receiving sequential clofarabine and lenalidomide for high risk MDS and AML in a phase I study. Our results highlight the potential of immune profiling for monitoring immune-modifying agents in high risk MDS and AML.